Emitter clogging when using water from a tributary of the Bogota River in Colombia (2016)
An experiment was conducted to study the behavior of three types of emitters used in Colombia under real-work conditions using water from the Neusa River, a tributary of the Bogota River. The emitters included: an in-line turbulent-flow emitter (E1), an integrated turbulent-flow emitter (E2), and an integrated self-regulated turbulent-flow emitter (E3). The operation and quality of the emitters were evaluated taking into account the flow decrease trend over time (RF), the flow reduction percentage of the emitters (qr), the coefficient of variation (Cv), the Christiansen uniformity coefficient (CU), and the emission uniformity (EU). The results indicated that the water quality in general affected the performance of the emitters over time, depending on the characteristics and properties of the emitters. The EU and CU decreased in the three emitter types as the experiment progressed and the Cv and qr increased. The E2 emitter showed a lower Cv and qr and a higher CU and EU than the E1 and E3 emitters.